2011
DOI: 10.1007/s00253-011-3699-z
|View full text |Cite
|
Sign up to set email alerts
|

Nanotube-supported bioproduction of 4-hydroxy-2-butanone via in situ cofactor regeneration

Abstract: Nicotinamide cofactor-dependent oxidoreductases have been widely employed during the bioproduction of varieties of useful compounds. Efficient cofactor regeneration is often required for these biotransformation reactions. Herein, we report the synthesis of an important pharmaceutical intermediate 4-hydroxy-2-butanone (4H2B) via an immobilized in situ cofactor regeneration system composed of NAD(+)-dependent glycerol dehydrogenase (GlyDH) and NAD(+)-regenerating NADH oxidase (nox). Both enzymes were immobilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Similar results were observed if the GlyDH from Escherichia coli was coupled to NOX from Bacillus cereus to produce 4-hydroxy-2-butanone from 1,3-butanediol. [22] We also tested different CAT/GlyDH ratios with a constant NOX/GlyDH ratio of 4. A CAT/GlyDH ratio between 250 and 1000 achieved 12 % of the DHA theoretical yield (Figure 1 B), whereas the multienzyme system that lacked CAT was able to produce only 8 % of the DHA theoretical yield.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were observed if the GlyDH from Escherichia coli was coupled to NOX from Bacillus cereus to produce 4-hydroxy-2-butanone from 1,3-butanediol. [22] We also tested different CAT/GlyDH ratios with a constant NOX/GlyDH ratio of 4. A CAT/GlyDH ratio between 250 and 1000 achieved 12 % of the DHA theoretical yield (Figure 1 B), whereas the multienzyme system that lacked CAT was able to produce only 8 % of the DHA theoretical yield.…”
Section: Resultsmentioning
confidence: 99%
“…Such in vitro processing of sugars may allow a new route for biohydrogenation reactions. Another in vitro system used non-covalent immobilization of a cofactor regeneration system on functionalized single-walled carbon nanotubes to make the pharmaceutical intermediate 4-hydroxy-2-butanone [12].…”
Section: Cofactor Considerations In Metabolic Engineeringmentioning
confidence: 99%
“…Some examples illustrating the requirement for cofactor balance and availability include: the conversion of biomass feedstocks containing xylose to ethanol where the formation of xylitol is a problem [1][2][3][4][5][6][7]; as a driving force for more effective production of reduced compounds such as biofuels [8]; in using cytochrome P450s in specific oxidation reactions where the recycling of active enzyme is required [9][10][11]; and the production of chiral pharmaceutical intermediates where specific reductions require a certain cofactor [12,13]. Experimental studies along with more complete computational models have shown a global picture of the flow of reducing equivalents and its connection to cell physiology and allowed these insights to be considered for metabolic engineering purposes [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…modified single-walled carbon nanotubes (SWCNTs) (Fig. 2), multi-walled carbon nanotubes (MWCNTs), nanospheres, and showed more than 80 % activity retention and notable stability improvement ( [42][43][44][45]). In these cases, nanostructures were first treated with acid mixture (HNO 3 / H 2 SO 4 : 1:3) to have -COOH groups on their surface, and added to NHS/ECS to form nanomaterial-NHS ester complex.…”
Section: Polyhistidine-co 2? /Ni 2?mentioning
confidence: 98%
“…The NOX loading capacity on the modified SWCNTs (0.47 mg enzyme/mg SWCNTs) was found much higher than that of using commercially available Sepharose beads (0.01 mg enzyme/mg Sepharose beads). When the immobilized NOX and glycerol dehydrogenase were both employed in a cofactor regeneration system to produce 4-hydroxy-2-butanone (4H2B), the 4H2B yield increased to 37 % as compared 17 % of free enzyme system, which was mainly due to the enhanced enzyme stability at the reaction temperature [42].…”
Section: Polyhistidine-co 2? /Ni 2?mentioning
confidence: 99%